Gender agreement violations modulate beta oscillatory dynamics during sentence comprehension: A comparison of second language learners and native speakers. (August 2016) - Lewis, Ashley Glen; Lemhӧfer, Kristin; Schoffelen, Jan-Mathijs; Schriefers, Herbert
Abstract: For native speakers, many studies suggest a link between oscillatory neural activity in the beta frequency range and syntactic processing. For late second language (L2) learners on the other hand, the extent to which the neural architecture supporting syntactic processing is similar to or different from that of native speakers is still unclear. In a series of four experiments, we used electroencephalography to investigate the link between beta oscillatory activity and the processing of grammatical gender agreement in Dutch determiner-noun pairs, for Dutch native speakers, and for German L2 learners of Dutch. In Experiment 1 we show that for native speakers, grammatical gender agreement violations are yet another among many syntactic factors that modulate beta oscillatory activity during sentence comprehension. Beta power is higher for grammatically acceptable target words than for those that mismatch in grammatical gender with their preceding determiner. In Experiment 2 we observed no such beta modulations for L2 learners, irrespective of whether trials were sorted according to objective or subjective syntactic correctness. Experiment 3 ruled out that the absence of a beta effect for the L2 learners in Experiment 2 was due to repetition of the target nouns in objectively correct and incorrect determiner-noun pairs. Finally, Experiment 4 showed that when L2 learners are required to explicitly focus on grammatical information, they show modulations of beta oscillatory activity, comparable to those of native speakers, but only when trials are sorted according to participants' idiosyncratic lexical representations of the grammatical gender of target nouns. Together, these findings suggest that beta power in L2 learners is sensitive to violations of grammatical gender agreement, but only when the importance of grammatical information is highlighted, and only when participants' subjective lexical representations are taken into account. Highlights: Gender agreement violations lead to lower beta oscillatory power for native speakers. L2 only exhibit beta effects when grammatical information is task-relevant. Subjective representations of grammatical gender are most relevant for L2 learners. Number agreement violations do not result in beta power effects for either group.